1988
DOI: 10.1088/0029-5515/28/9/004
|View full text |Cite
|
Sign up to set email alerts
|

Beat wave current drive with intense pulsed free-electron lasers

Abstract: High power free-electron lasers make possible new methods for driving current in toroidal devices with electromagnetic waves. Earlier considerations of beat wave current drive are applied to a hot magnetized plasma and an arbitrary beat wave. Here the beating of two electromagnetic waves resonantly excites a low frequency beat wave that accelerates and heats electrons and leads to a current. The absolute current drive efficiency depends nonlinearly on the two pump wave intensities and is constrained by the Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…In the limit relevant to this experiment, Ra^l, with p-1 the above relationship reduces to R a -pJo. Simulation results indicate that when the plasma wave phase velocity is less than -1.5v e , the momentum in the wave is efficiently coupled to the electrons [3]. Consistent with the simulation results, energetic electrons were only measured when tfph < 7iv, although electrostatic waves were measured at higher phase velocities.…”
Section: )-{ Ln[(\-r a )(P+r A )/P]supporting
confidence: 79%
See 1 more Smart Citation
“…In the limit relevant to this experiment, Ra^l, with p-1 the above relationship reduces to R a -pJo. Simulation results indicate that when the plasma wave phase velocity is less than -1.5v e , the momentum in the wave is efficiently coupled to the electrons [3]. Consistent with the simulation results, energetic electrons were only measured when tfph < 7iv, although electrostatic waves were measured at higher phase velocities.…”
Section: )-{ Ln[(\-r a )(P+r A )/P]supporting
confidence: 79%
“…There has been no previous experimental testing of beat-wave current drive primarily because of the lack of very high intensity millimeter wave sources which are necessary to achieve high current drive efficiency in a tokamak [3]. In the experiment described below, counterpropagating microwaves were launched in a toroidal plasma with only a toroidal magnetic field and no initial plasma current.…”
mentioning
confidence: 99%
“…The maximum amplitude of the driving force and the minimum thermal velocity are determined by condition (13). The growth of the norm at high plasma temperature is caused by approaching the limits (16) and (17). The relatively poor accuracy of the fluid model at small amplitude of the driving force can be explained by long time of the linear regime of Landau damping.…”
Section: Numerical Verification Of Simplified Fluid Modelmentioning
confidence: 99%
“…For example, the plasma wave can be driven parametrically. Potentially, this study is relevant to the problems of: laser reflectivity in NIF-like conditions (see, for example, [15]), backward Raman amplifier in plasma [16], and Raman current drive [17]. The purpose of this paper is to develop and to verify a simple model of nonlinear Landau damping, which can quantitatively describe the class of problems mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…In laser fusion, even a small number of energetic electrons can cause severe preheating and degrade the gain of the fusion target [1]. In magnetic fusion, it was recently suggested that the so-called beat-wave process [2] or SRS [3] in the microwave region could be used for current drive in tokamaks. In this application, the fast electrons are beneficial because they are almost collisionless, which improves the current drive efBciency.…”
mentioning
confidence: 99%